Death, trauma and grief: the case of the prison. (3rd April 2023) - Sim, Joe
ABSTRACT: This paper critically analyses deaths in prison in England and Wales. It focuses on how the state's 'truth' about the nature and extent of these deaths has been challenged and develops an alternative perspective which situates these deaths in the context of a system built on violence and systemic indifference and where state agents are protected by a culture of immunity and impunity. It also illustrates the often-abysmal treatment of the families of dead prisoners and the struggles they have engaged in, alongside the charity INQUEST 1, to establish the actual truth about the deaths of their relatives and to hold to account those responsible for these deaths, many of which were preventable. The paper concludes by outlining a range of radical alternatives to the current baleful situation including humanising prisoners and removing the stigma of less eligibility which has prevailed for 200 years and has legitimated the pain and punishment inflicted on them by the state.